The Gossypium longicalyx Genome as a Resource for Cotton Breeding and Evolution. Issue 5 (1st May 2020) - Grover, Corrinne E; Pan, Mengqiao; Yuan, Daojun; Arick, Mark A; Hu, Guanjing; Brase, Logan; Stelly, David M; Lu, Zefu; Schmitz, Robert J; Peterson, Daniel G; Wendel, Jonathan F; Udall, Joshua A
Abstract: Cotton is an important crop that has made significant gains in production over the last century. Emerging pests such as the reniform nematode have threatened cotton production. The rare African diploid species Gossypium longicalyx is a wild species that has been used as an important source of reniform nematode immunity. While mapping and breeding efforts have made some strides in transferring this immunity to the cultivated polyploid species, the complexities of interploidal transfer combined with substantial linkage drag have inhibited progress in this area. Moreover, this species shares its most recent common ancestor with the cultivated A-genome diploid cottons, thereby providing insight into the evolution of long, spinnable fiber. Here we report a newly generated de novo genome assembly of G. longicalyx . This high-quality genome leveraged a combination of PacBio long-read technology, Hi-C chromatin conformation capture, and BioNano optical mapping to achieve a chromosome level assembly. The utility of the G. longicalyx genome for understanding reniform immunity and fiber evolution is discussed.